COMPARATIVE ANALYSIS OF PUBLIC RELATIONS STRATEGIES IN LOKOJA AND ANKPA LOCAL GOVERNMENT AREAS, KOGI STATE, NIGERIA - JIBRIN UMAR OMACHI; EZEKIEL S. ASEMAH; DANIEL O. EKHAREAFO (International Studies Journal)
This study is a Comparative Analysis of Public Relations Strategies in Select Local Governments in Kogi State, Nigeria. It comparatively examined the public relations strategies employed by Lokoja and Ankpa Local Government Areas in Kogi State, Nigeria, and assessed their effectiveness in managing relationships with stakeholders and fostering community engagement. The Communication Accommodation Theory (CAT) was used as the theoretical framework. A qualitative research approach was employed, involving in-depth interviews with 20 key stakeholders, including Public Relations Officers (PROs), Local Government Chairmen, Councilors, Directors of Administration, and Heads of Departments (HODs) responsible for public relations and communication. The findings revealed that Lokoja's proactive approach, characterized by community engagement and the use of digital communication, has fostered transparency and trust among residents, while Ankpa's reactive strategy has highlighted significant gaps in communication and engagement. The study concluded that public relations strategies play a crucial role in shaping the effectiveness of local governance in Kogi State. It is recommended that Lokoja Local Government Area strengthens its mechanisms for gathering and responding to community feedback, while Ankpa Local Government Area should prioritize the development of a comprehensive public relations strategies that incorporate both traditional and digital communication methods. Recommendations are also made for local government areas to adopt proactive public relations strategies that prioritize community engagement and transparency.